Quality assessment of semolina pasta incorporated with Gracilaria sp. - Gulmatico, R.L. Christian Glendon Hubero
This study intended to improve the quality of semolina pasta through the incorporation of Gracilaria sp. The proximate analysis for semolina obtained a moisture content of 12.3%, 1.31% crude fat, 21.0% crude protein, 0.60% crude fiber, 0.80% crude ash, and carbohydrate content of 65.3%. Gracilaria sp. had a moisture content of 89%, crude fat of 0.89%, 9.56% crude protein, 2.89% crude fiber, and 14.58% crude ash, and carbohydrate content of 24.78%. Three formulations of semolina-Gracilaria sp. pasta were used: Formulation 3 (5% Gracilaria sp.). Constant amount of salt, water, egg were added to the three formulations. Formulation 3 was the most preferred among the semolina-Gracilaria sp. pasta formulations by Rank Sum test at 5% level of significance. It was generally accepted as ?like moderately?, and described as firm, no perceptible seaweed odor and flavor, and bright light yellow color. No significant differences were found between the most seaweed-Gracilaria sp. pasta and control in terms of proximate content (moisture, crude fat, crude protein, crude fat, crude ash, crude fiber) and pH except for the microbiological test based on total plate count as well as carbohydrate content, where there was a significant decrease when Gracilaria sp. was added with the semolina pasta. All of the proximate composition of the semolina pasta increased when Gracilaria sp. was added, although the increase was not significant.